Biomass production and essential oil composition of Thymus vulgaris in response to water stress and harvest time. Issue 1 (2nd January 2019) - Said-Al Ahl, Hussein A. H.; Sabra, Ali S.; Alataway, Abed; Astatkie, Tess; Mahmoud, Abeer A.; Bloem, Elke
ABSTRACT: A greenhouse experiment was conducted to study the effects of irrigation interval (4, 8, 12 and 16 days) and harvest (2, 4, 6, 8, 10 and 12 months after transplanting) on biomass, essential oil (EO) content and composition of Thymus vulgaris . As irrigation interval increased, herb fresh and EO yield decreased, but EO content increased, suggesting water stress stimulates EO content. While fresh weight peaked at 4 months, EO content and yield peaked at 6 months; then they declined and reached the bottom at 12 months. Thymol, p-cymene and γ-terpinene were the major compounds in T. vulgaris . The highest γ-terpinene and p-cymene were obtained when harvested at 12 months. The highest thymol was obtained when harvested at 2 months and irrigated every 4 days. This study showed biomass, EO content, yield and the accumulation of EO constituents of T. vulgaris are influenced by irrigation interval and harvest in different ways.